2021
DOI: 10.1177/01632787211049273
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Affecting Health-Related Quality of Life in Women With Chronic Multisite Musculoskeletal Pain: A Cross-Sectional Study in Ankara, Turkey

Abstract: Although chronic multi-site musculoskeletal pain is known to cause decreased physical function and impair work and social life, there is insufficient research about its impact on health-related quality of life (HRQoL) in women. The aim of this study was to investigate multiple factors affecting HRQoL in women with chronic multi-site musculoskeletal pain. This study included 227 women with two or more musculoskeletal areas which were painful during the last 3 months. The HRQoL and musculoskeletal system symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Previous studies that investigated factors affecting QOL in patients with chronic pain reported two major findings. First, a study involving women with chronic multi-site musculoskeletal pain found that sociodemographic characteristics along with social and psychological factors may affect health-related QOL (28). Second, the multidimensional negative impact of chronic pain, such as interference of physical functioning, professional life, relationships, family life, social life, sleep, and mood, leads to poorer QOL (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that investigated factors affecting QOL in patients with chronic pain reported two major findings. First, a study involving women with chronic multi-site musculoskeletal pain found that sociodemographic characteristics along with social and psychological factors may affect health-related QOL (28). Second, the multidimensional negative impact of chronic pain, such as interference of physical functioning, professional life, relationships, family life, social life, sleep, and mood, leads to poorer QOL (29).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, our study focused solely on patients with chronic musculoskeletal pain who provided valid questionnaire responses. Conversely, prior reports included studies such as one that exclusively involved female patients with chronic multi-site musculoskeletal pain in Turkey (28), and another that encompassed patients with chronic pain, predominantly experiencing lower back pain followed by lower limb pain, in the North of England (29).…”
Section: Resultsmentioning
confidence: 99%
“…There were no differences between participants with and without fear-avoidance behaviours in terms of age, BMI, pain intensity, presence of moderate or definite depression. The fear-avoidant group had longer duration of pain and had higher disability scores; 10 years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)[median (25-75% IQR)] vs 3.25 years (0.5-10)[median (25-75% IQR)] and 19 (16)(17)(18)(19)(20) [median (25-75% IQR)] vs 11.5 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)[median (25-75% IQR)] points from the Roland Morris Disability Questionnaire (p = 0.028), (p = 0.008) respectively. Table 2 shows a comparison of participants with and without fear-avoidance behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…32 According to the researchers' findings, employment hours do not correlate with the working "mothers" quality of life in the current study; a significant association between the employment status of mothers being employed having a better quality of life for working women than for unemployed women was established in literature. 29,33 Moreover, another study showed that older Koreans' quality of life is greatly impacted by work. 34 Regarding BMI, the current findings Contrary to most of the literature, increased body mass index (BMI) was negatively related to the quality of life in the general Turkish population; 33 lend support to this result in a study from the USA, 2 like that of Kuwait.…”
Section: Discussionmentioning
confidence: 99%